The Effect of Interpersonal Relationships and Motivation on Contextual Performance at PT. Bank Negara Indonesia (Persero) Tbk. Mattoangin Makassar Main Branch Office - Andi Muh. Wahidien S Alam; Muh. Yunus Amar; Andi Reni (Scientia Integritas Utama, 2023)
In a company, there is an interpersonal relationship. Interpersonal relations can be interpreted as relationships between a person and other people. From the psychology of communication, the better the interpersonal relations, the more open people are to express themselves, and the more accurate their perceptions of other people and their self-perceptions are, the more effective the communication between communicants. This study aimed to determine the effect of interpersonal relationships and motivation on contextual performance at PT. Bank Negara Indonesia (Persero) Tbk. Main Branch Office Mattoangin Makassar. The analytical methods used in this study are multiple linear regression analysis, validity test, reliability test, and partial test (t). The results of the study using various regression analyses obtained an identifiable coefficient of 0.540 which indicates that the magnitude of the contribution given by the independent variable, namely the interpersonal relationship variable (X1) and motivation (X2), to the dependent variable, i.e. contextual performance (Y), is equal to 54%. This means that the level of change in the independent variable, namely contextual performance (Y), can be explained by changes in the independent variables, namely interpersonal relations (X1) and motivation (X2) of 54%. In comparison, the remaining 46% is influenced by other factors not examined in this study. Based on the analysis results, interpersonal relations and motivation have a significant effect on contextual performance, meaning that if good interpersonal relationships and motivation exist between employees, contextual performance can improve